2022
DOI: 10.3389/fimmu.2022.853094
|View full text |Cite
|
Sign up to set email alerts
|

miR-582 Suppresses the Proliferation of B-Cell Precursor Acute Lymphoblastic Leukemia (BCP-ALL) Cells and Protects Them From Natural Killer Cell-Mediated Cytotoxicity

Abstract: B-cell precursor acute lymphoblastic leukemia (BCP-ALL) is a malignancy characterized by the aberrant accumulation of immature B-cell precursors in bone marrow and other lymphoid organs. Although several intrinsic regulatory signals participating in BCP-ALL have been clarified, detailed intrinsic and extrinsic mechanisms that regulate BCP-ALL progression have not been fully understood. In the current study, we report that miR-582 is downregulated in BCP-ALL cells compared with normal B cells. Forced overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…A study on leukemic cells in 5 patients with B-cell precursor ALL (BCP-ALL) also showed that microRNA582 inhibits the cytotoxic effects of NK cells on leukemic cells by inducing the CD276 (B7-H3) checkpoint. Therefore, it is suggested that blockade of CD276 or its ligand on NK cells may be a potential therapeutic approach in leukemia [ 90 ]. In addition to the discussed inhibitory checkpoints, Rothfelder et al .…”
Section: Exhausted Nk Cells and Leukemiamentioning
confidence: 99%
“…A study on leukemic cells in 5 patients with B-cell precursor ALL (BCP-ALL) also showed that microRNA582 inhibits the cytotoxic effects of NK cells on leukemic cells by inducing the CD276 (B7-H3) checkpoint. Therefore, it is suggested that blockade of CD276 or its ligand on NK cells may be a potential therapeutic approach in leukemia [ 90 ]. In addition to the discussed inhibitory checkpoints, Rothfelder et al .…”
Section: Exhausted Nk Cells and Leukemiamentioning
confidence: 99%
“…Li et al [38] observed that miR-582 overexpression increased NK cell-mediated cytotoxicity with B-cell precursor acute lymphoblastic leukemia cells upregulating the expression of B7-H3 (CD276), which is a newly discovered member of the B7 family that could promote T cell activation [61,62].…”
Section: Mirnas That Modulate Response To Icismentioning
confidence: 99%